2022
DOI: 10.1093/jbcr/irac180
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Complications in Patients With Severe Frostbite Injury

Abstract: Frostbite is caused by exposure to cold temperatures and can lead to severe injury resulting in amputations. Tissue plasminogen activator (tPA) is a thrombolytic agent that has demonstrated efficacy preventing amputation in frostbite patients. The goal of frostbite management with tPA is to salvage tissue without causing clinically significant bleeding complication. The purpose of this study was to characterize bleeding complications in severe frostbite patients managed with and without tPA. Retrospective char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Use of thrombolytics is associated with a risk of hemorrhage. A study of bleeding complications in patients with severe frostbite treated using intravenous tPA found that 8% of patients developed bleeding that necessitated changes in management [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Use of thrombolytics is associated with a risk of hemorrhage. A study of bleeding complications in patients with severe frostbite treated using intravenous tPA found that 8% of patients developed bleeding that necessitated changes in management [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the early 1990s, the Hennepin County Medical Center in Minneapolis piloted the use of thrombolytics in the treatment of frostbite [ 12 ]. Thrombolytics or recombinant tissue plasminogen activators (rtPA) work by binding to fibrin in a thrombus and activating plasminogen, which causes local fibrinolysis and prevents enlargement of blood clots in frostbitten extremities [ 13 ]. Several thrombolytics, mainly alteplase, have been used in the treatment of frostbite with over 15 published studies, totalling over 300 patients [ 4 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thrombolytics carry a risk of bleeding and haemorrhage. In a recent study detailing bleeding complications in severe frostbite patients treated with intravenous alteplase, 8.4% of patients had bleeding resulting in change of management or intervention [ 13 ].…”
Section: Introductionmentioning
confidence: 99%